Effect of Artemisia rupestris L. Extract on Gastrointestinal Hormones and Brain-Gut Peptides in Functional Dyspepsia Rats. (17th November 2020) - Wang, Chun; Wang, Bin; Aili, Maimaiti; Huo, Shixia; Han, Meng-ting; Aibai, Silafu; Li, Zhi-Jian
Abstract : Artemisia rupestris L. is the perennial herb of rupestris belonging to Artemisia (Compositae), which is wildly distributed in Xinjiang (China), middle Asia, and Europe. It is known to have anti-inflammatory, hepatoprotective, immune function regulation, and gastrointestinal function regulation effects. AR is used to treat digestive diseases, but the effects of AR on antifunctional dyspepsia (FD) activity have not yet been reported. In this study, we aimed to investigate the therapeutic effects of Artemisia rupestris L. extract (ARE) on gastrointestinal hormones and brain-gut peptide in functional dyspepsia (FD) rats. Sixty Sprague-Dawley rats were randomly divided into 6 groups. An FD rat model was established by irregular tail clamp stimulation for 14 days except the blank group. After FD rat models, the blank group and model group were given menstruum, and the medicated rats were given corresponding medicine for 14 days. The general observations, bodyweight, and food intake were observed, and the content of serum gastrin (GAS), plasma motilin (MTL), plasma vasoactive intestinal peptide (VIP), and plasma somatostatin (SS) by the enzyme-linked immunosorbent assay was observed. The content of plasma VIP and plasma SS in the ARE group was significantly lower than in the model group, and the content of serum GAS and plasma MTL was increased in the ARE group; the GAS expression of antrum and hypothalamus was increased in the ARE group, and SS expression of antrum and hypothalamus was decreased in the ARE group by immunohistochemical detection; the results of semiquantitative reverse transcription polymerase chain reaction (RT-PCR) indicate that ARE inhibits the mRNA expression of VIP. Our results suggest that ARE can recover gastrointestinal hormone levels and regulation of the peripheral and central nervous system and alter gut peptide levels, which confirm the therapeutic effect of ARE on functional dyspepsia.